Triandis' theory of interpersonal behaviour in understanding software piracy behaviour in the South African context. - Robinson, Julie (My University, 2010)
The aim of this research study was to explore whether a revised version of Triandis’ (1977) Theory of Interpersonal Behaviour would provide an understanding of software piracy behaviour within the South African context. As South Africa has a high intention to pirate software but at the same time has one of the lowest proportions of software piracy in comparison to the rest of the world, this study employed a slightly modified version of Triandis’ TIB in order to determine what the objective factors present in the external environment are that enable this behaviour to be performed with either ease or difficulty. In order to address this, the study employed a quantitative, non-experimental and cross-sectional research design. A questionnaire compiled of previously developed scales measuring perceived consequences, social factors, affect, intentions, habit, facilitating conditions and behaviour was assembled in order to address the research question and eight hypotheses. All scales had good reliabilities that ranged between .76 and .92 and were measured on a 4 point likert type scale. An online survey was designed on SurveyMonkey and a link was placed on IT Web’s website for a period of six weeks. The sample size was 310 and consisted of a wide array of people who varied in terms of gender, age, race and occupation, including vast differences with regards to employment status, field of expertise and industry sector. Results provided sufficient evidence to suggest that affect, perceived consequences and social factors were all significantly and positively related to intention. The results also indicated that intention and habit are both able to predict software piracy behaviour. However, high intention and strong habit weighting do not always lead to the execution of behaviour. Therefore, the study demonstrated that facilitating conditions play an important role in determining whether a desired behaviour will be carried out or not. The findings illustrate that facilitating conditions and habit both moderate the intention-behaviour relationship and facilitating conditions moderates the habit-behaviour relationship. This study provided support for Triandis TIB with regards to its predictive power for gaining an understanding of software piracy behaviour. Practical and theoretical implications of these results are discussed as well as the areas in which anti-piracy campaigns can continue to become more focussed and directed in order to contribute to the reduction in South Africa’s piracy rate.